Numerical analysis of lasing dynamics in volume free electron laser - Sytova, Svetlana (Mathematical Modelling and Analysis, 2008)
Nonlinear phenomena originating in volume free electron laser (VFEL) are investigated by methods of mathematical modelling using computer code VOLC. It was demonstrated the possibility of excitation of quasiperiodic oscillations not far from threshold values of electron beam current density and VFEL resonator length. It was investigated sensibility of numerical solution to initial conditions for different VFEL regimes of operation. Parametric maps with respect to electron beam current and detuning from synchronism condition present complicated root to chaos with windows of periodicity in VFEL. Investigation of chaotic lasing dynamics in VFEL is important in the light of experimental development of VFEL in Research Institute for Nuclear Problems.First Published Online: 14 Oct 2010